SPRAWLING PATTERN OF HOUSING DEVELOPMENT IN JATI AGUNG DISTRICT, SOUTH LAMPUNG REGENCY - Balqis, Nadya Fatrah; Wiranegara, Hanny Wahidin; Taki, Herika Muhammad (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2022)
In Jati Agung Subdistrict, South Lampung Regency is a sprawling housing development. This subdistrict is directly adjacent to Bandar Lampung, the province’s capital city. This study aims to identify the sprawling pattern of housing development in the sub district of Jati Agung due to its unfavorable impacts such as land use irregularities, infrastructure inefficiencies, and environmental problems. There are three patterns of sprawling: clustered, random, and uniform. The analytical method used to identify the patterns is nearest neighbor analysis. This analysis was to measure the housing distribution pattern by calculating the size of the nearest neighbor (T) parameter. The nearest neighbor distribution index (T) is calculated using the variable distance of the nearest point (Ju), the number of settlement points (N), and the area (A). The results are as follows: the sprawling pattern in majority villages is random and uniform. To control this sprawl, local governments can use permits, incentives/disincentives, and ratification of detailed spatial planning. patterns of sprawling, namely clustered, random, and uniform. The analytical method used to identify the patterns is nearest neighbor analysis. Variables used in this method are the distance to the nearest point, the number of housing points, and the area. The results are as follows: the sprawling pattern in majority villages is random and uniform. To control this sprawl, local governments can be used permits, incentives/disincentives, and ratification of detail spatial planning. Keywords: sprawling pattern, housing development, nearest neighbor analysis, Jati Agung Subdistrict